A combined modelling approach to design test structures to study thermomigration in Cu interconnects. (November 2022) - Ding, Y.; Lofrano, M.; Varela Pedreira, O.; Zahedmanesh, H.; Croes, K.; De Wolf, I.
Abstract: With the downscaling of microelectronic devices, thermal gradients become increasingly important, making thermomigration (TM) an important mass transport mechanism. We use a combination of thermal simulations using finite element (FE) methods and a 1D physics-based TM model to characterise and design test structures to study thermomigration in Cu interconnects. As the test structure, in order to locally heat a section of the Cu interconnect, we propose to add a W-heater below a classical electromigration (EM) test structure. Using experimentally calibrated FE thermal models, we study the temperature distribution and temperature gradients along the Cu interconnects for various configurations of the test structure. Subsequently, the 1D TM model is used to identify locations where the tensile stress would reach a critical stress, σ crit, which can lead to void nucleation induced by thermal gradients. By comparing different heater positions, we show that a higher thermal gradient is expected when the heater is positioned further away from the local heat sinks. Based on the outcome of the simulations, we propose a modified test structure where metal levels are inverted such that the Cu metal line is closer to the heater. Such structure shows a 4× increase in temperature gradient compared to the original structure, facilitating TM characterisation studies. Highlights: A combination of thermal simulations using FE methods and a 1D TM model to characterise and design test structures to study thermomigration in Cu interconnects. Experimentally calibrated finite element (FE) thermal models are used to extract the temperature and temperature gradients distribution along the Cu interconnects. 1D physical-based TM model can identify the locations for voiding induced by thermal gradients. By comparing different heater positions, we show a 4x increase in thermal gradient when the heater is positioned further away from the local heat sinks. A modified test structure by inverting metal level to close to the heater predicts another 4x increase in thermal gradient and a 77x faster reach of the critical stress level for void formation.